EMPOWERING UMKM THROUGH DIGITAL MARKETING: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (ADISAM Publisher, 2024)
The empowerment of Micro, Small and Medium Enterprises (MSMEs) through digital marketing is becoming an increasingly relevant topic in the context of technological development and globalisation. The purpose of this literature review is to understand the impact and benefits offered by digital marketing for MSMEs. The literature analysed shows that digital marketing allows MSMEs to reach a wider market at a lower cost than traditional methods. In addition, digital marketing provides the ability to target audiences more specifically, as well as providing analytics tools to monitor marketing performance in a timely manner. Another advantage identified is the improvement of MSME entrepreneurs' skills and knowledge of digital technology, which in turn increases their capacity and competence in innovating and developing products. By utilising digital marketing, MSMEs can become more competitive and resilient in the face of fast-changing market dynamics. This digital transformation not only supports inclusive economic growth but also strengthens the overall MSME business ecosystem, positively contributing to their sustainability and future development.